2011
DOI: 10.1111/j.1472-765x.2011.03139.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa in a hydropathic facility: diversity, susceptibility and imipenem resistance mutation

Abstract: Aims:  To detect Pseudomonas aeruginosa in water and treatment equipment biofilms of a thermae hydropathic facility and to study antibiotic susceptibility and genetic diversity. Methods and Results:  One hundred and fifty‐four planktonic isolates were obtained from 2220 water samples during 4 years. Seventy‐two biofilm isolates were obtained from 23 samples of inner parts of three inhalation equipments. Antibiotic susceptibility was determined by disc diffusion. All isolates were susceptible to tested antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…More than 21 million European patients use this natural therapy (Pereira et al . ), and literature indicates that the majority of thermae users present risk factors to pneumonia (Vinogradova et al . ; Portuguese Spas Association ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More than 21 million European patients use this natural therapy (Pereira et al . ), and literature indicates that the majority of thermae users present risk factors to pneumonia (Vinogradova et al . ; Portuguese Spas Association ).…”
Section: Discussionmentioning
confidence: 99%
“…This natural practice is very frequent in Europe, with more than 21 million users (Pereira et al . ). Treatments are performed using equipments similar to the hospital ventilators, and thermae users deep inhale aerosol particles of undisinfected NMW for about 15–20 min on a daily basis, typically during 7–14 consecutive days.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A probiotic strain, Lactobacillus plantarum P-8, caused a shift in the faecal bacterial profile in humans, and this shift has been suggested to be due to the putative plantaricin production by this strain [92]. In another study, nisin F has been suggested to have a stabilizing effect on the bacterial populations in the gut of mice [93]. These studies illustrate the impacts of bacteriocins on the gut microbiota; however, they vary greatly in terms of the administration method, the model used in the experimental design and the use of proper negative controls.…”
Section: Bacteriocinsmentioning
confidence: 99%